Kinematics Analysis and Parameter Optimization of a Novel 3T1R Parallel Robot Mechanism - Huajuan Xu; Hongwei Li; Chunyan Zhang (Jixie chuandong)
Based on the design theory of position and orientation characteristic set， a kind of parallel robot mechanism is proposed， whose moving platform can realize three translations and one rotation. According to the orientation characteristic equation， the topological structure of the mechanism is analyzed， and the kinematics equation model is established by the constraint condition of the length of the rod， and the forward and inverse solution analysis is completed. The motion conditions of singular configuration are determined according to the Jacobian matrix. The operation space shape and rotation flexibility of the moving platform of the mechanism are further studied. At the same time， according to the single variable method， the influence of structural parameters on the operation space is analyzed. The optimization model of operation space maximization is established， the scale optimization is carried out by using beetle antennae search algorithm with fast search speed and strong global search ability. The results show that the mechanism has large， regular shape workspace and strong rotation ability， and the optimized size parameters provides a theoretical basis for the application design of the manipulator.